The Influence of Neural Computing Engineering and AI on Social Media User Behavior and Decision Making - Muna Nama Thweny; Hamid Sh. Aldulami; Laith M Fawzi; Ammar Abdullatif Hadi; Zeyad Ibrahim Bakri (Decision Making: Applications in Management and Engineering, 2025)
The objective of this study was to investigate the impact of received personalization of content, perceived algorithm transparency and perceived ethical concerns on user decision-making behaviour on social media (SM). For this purpose, quantitative data from the primary resources was collected and this study used RStudio for robust analysis. The population of this study was SM users from USA, Canada, United Kingdom, Brazil, India, Australia, Japan and Germany. A sample of 395 respondents was analysed, and the findings of this study highlight the impact of received personalization of content, perceived algorithm transparency and perceived ethical concerns on user decision-making behaviour on SM is positive and significant. The study has significant implications for the body of knowledge where the identified gaps were addressed. In addition, this study provides practical implications how the users can avoid the influence of SM to influence on their decision-making behaviour.